AB0801 Sarcopenia and microcirculation in systemic sclerosis patients: a pilot assay. (12th June 2018) - Paolino, S.; Tomatis, V.; Casabella, A.; Pizzorni, C.; Sulli, A.; Ghio, M.; Ruaro, B.; Alessandri, E.; Pendolino, M.; Cosso, C.; Ferrari, G.; De Gregorio, S.; et al.
Abstract : Background: Systemic sclerosis (SSc) patients may present muscle involvement in the form of myositis or non-inflammatory myopathy with different degree of weakness and muscle atrophy. 1 Sarcopenia is described as a multifactorial syndrome with muscle mass loss associated to functional impairment; according to the anthropometric equation by Baumgartner et al. sarcopenia was defined as relative skeletal muscle mass index (RSMI) <5.5 Kg/m 2 for women and <7.26 Kg/m 2 for men. The relationships between sarcopenia and other clinical aspects in SSc are poor investigated. Objectives: The aim of the study was to evaluate the associations between sarcopenia and other clinical factors in SSc patients. Methods: 20 female patients fulfilling the ACR 2013 criteria for SSc (mean age 61.7±13.6 years, disease duration 86.2±67.1 months) were enrolled. The RSMI (Kg/m 2 ) was evaluated by dual-energy X-ray absorptiometry scan (Lunar Prodigy). Nail fold videocapillaroscopic (NVC) patterns ( early, active, late ) were analysed. Serum 25(OH)2 D concentration was tested by immunofluorescence. Non parametric statistical tests were used. Results: Patients showed a modified Rodnan skin score (mRSS) 12.2±7.7, RSMI 6.01±0.97 Kg/m 2, serum vitamin D (25(OH)2 D) 22.01±13.1 ng/dL and CPK 70.16±31.8 U/L. In this cohort 23% of SSc patients were found affected by sarcopenia, and almost 42% showed the most advanced level of microvascular damage, as characterised by the NVC late pattern. However, no statistically relevant correlations was observed between RSMI, BMI, age, disease duration, CPK, mRSS, 25(OH)2 D and active or late NVC patterns. Comparing age, disease duration, CPK and mRSS in both sarcopenic and non sarcopenic SSc patients there was no difference between the groups, however sarcopenic patients showed statistically significant lower BMI (p=0.02), lower RSMI (p=0.0008 and higher 25(OH)2 D serum concentrations (p=0.01). Particularly, RSMI showed a strong negative correlation with age (p=0.01). No statistical differences were found when grouping the patients according to the positivity for serum anti-topoisomerase I Ab or according to cutaneous diffuse (dcSSc) or limited (lcSSc) systemic sclerosis. Conclusions: This pilot study suggests that sarcopenia seems present in almost 25% of the SSc patients, particularly in a condition of advanced microcirculation failure ( late NVC pattern), however does not seem to correlate with skin fibrosis or disease duration. The study had some limitations due to absence of control group and to the small patient sample analysed. Further larger studies would be necessary to better investigate the role of sarcopenia in SSc. Reference: [1] Ranque, B., Authier, F.J., Berezne, A., Guillevin, L., Mouthon, L., 2007. Ann. N. Y. Acad. Sci. 1108, 268–282 Disclosure of Interest: None declared